Evaluating Situation Assessment in Distributed Network Electricity Control. (December 2020) - W.Wiggins, Mark; Auton, Jaime; Sturman, Daniel
Situation assessment is a critical skill amongst electricity distribution controllers but can be difficult to assess in practice. In the present research, we adapted a psychometric approach based on the principle that expert situation assessment engages cue-based associations from memory. Using consortium norming, we acquired performance data from 320 network control operators for five network control-related tasks that comprised the electricity network service provider edition of the EXPERT Intensive Skills Evaluation (EXPERTise 2.0) software. Operators were distributed across 11 Distributed Network Service Providers (DNSP), with data collected over three phases. Data were examined across the three phases of data collection and suggest that DNSPs can monitor the situation assessment of network controllers at an individual and at an organisational level, affording the opportunity to identify changes in performance and implement remedial strategies as appropriate.